2011
DOI: 10.1111/j.1600-0625.2009.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of keratins in cutaneous epithelial tumors and related disorders - distribution and clinical significance

Abstract: Keratins are a highly diverse family of cytoskeletal proteins and important markers of epithelial cell differentiation. In this review, applying the new keratin nomenclature recently introduced, we summarize and discuss the distribution and significance of keratin patterns in cutaneous epithelial tumors in relation to the epithelial structures of normal human skin. The available literature data show that the analysis of keratin profiles broadens our understanding of the differentiation, nature and histogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 118 publications
(234 reference statements)
2
51
0
1
Order By: Relevance
“…For example, keratin 5 is expressed in the basal layer of the skin of higher vertebrates, which possess skin epidermis stem cells (Lersch and Fuchs, 1988;Moll et al, 1989;Byrne and Fuchs, 1993). Suprabasal layers are keratin 1-and 10-positive (Andreadis et al, 2001;Kurokawa et al, 2011). In higher vertebrates, skin wound healing has been well studied and described specific expression of Keratins (Coulombe, 2003;Pechter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, keratin 5 is expressed in the basal layer of the skin of higher vertebrates, which possess skin epidermis stem cells (Lersch and Fuchs, 1988;Moll et al, 1989;Byrne and Fuchs, 1993). Suprabasal layers are keratin 1-and 10-positive (Andreadis et al, 2001;Kurokawa et al, 2011). In higher vertebrates, skin wound healing has been well studied and described specific expression of Keratins (Coulombe, 2003;Pechter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that keratin and filaggrin expression in milia correspond to the more superficial section of the infundibulum and the outermost layer of the hair bulge, respectively. Furthermore, K15, a stem pluripotent cell marker, is expressed in the outermost layer in normal hair follicles (5). K15 was present in the outermost layer of the deeper section of cyst walls and hair germ structures in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…In normal hair follicles, K10 and K1 are expressed in the infundibulum and suprabasal epidermis (5). K14 is expressed in all layers of the outer root sheath and infundibulum and in the basal layer of the epidermis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A biopsied specimen was taken from the left lateral abdomen. Keratin expression was examined with keratin (K) 1, K7, K8, KIO, K14, K15, K16, K17, K18, K19, and K20, as described (7). Filaggrin expression was exarnined with an antibody reacting to profilaggrin and filaggrin, as described (7).…”
Section: Case Reportmentioning
confidence: 99%